Drug-induced aortitis in a patient with ovarian cancer treated with bevacizumab combination therapy - Kengo Hiranuma; Soshi Kusunoki; Kazunari Fujino; Takashi Hirayama; Tsuyoshi Ota; Yasuhisa Terao (Elsevier, 2018)
Objective: To review and evaluate drug-induced vasculitis, which is an extremely rare complication of chemotherapy. Case report: A 47-year-old woman with ovarian cancer developed aortitis during bevacizumab combination chemotherapy. Contract-enhanced CT showed concentric thickening of the descending aorta. Antibiotics were administered, but a repeat CE-CT scan showed no resolution of the aortitis. To treat the aortitis, she was started on oral prednisolone. A subsequent CE-CT scan showed no signs of aortitis. She was thus re-started on a modified chemotherapy regimen. Conclusion: Aortitis should be considered in patients receiving bevacizumab combination therapy who develop persistent fever and upper-abdominal pain. Contrast-enhanced CT is useful for detecting drug-induced aortitis. Keywords: Aortitis, Ovarian cancer, Bevacizumab, G-CSF